2015
DOI: 10.1097/mnh.0000000000000079
|View full text |Cite
|
Sign up to set email alerts
|

JAK inhibition and progressive kidney disease

Abstract: Purpose of review To review the role of JAK-STAT signaling in the progression of chronic kidney diseases. Recent findings The JAK-STAT pathway transmits signals from extracellular ligands, including many cytokines and chemokines. While these responses are best characterized in lymphoid cells, they also occur in kidney cells such as podocytes, mesangial cells, and tubular cells. JAK-STAT expression and signaling abnormalities occur in humans and animal models of different chronic kidney diseases. Enhanced exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 78 publications
4
50
0
Order By: Relevance
“…31,32 Jak1 is a membrane protein whose kinase activity targets STAT proteins that are subsequently translocated to the nucleus to target specific gene transcription. Although most intensively studied for their important roles in cytokine signaling, modulating the immune response and oncogenesis, mutations in the proteins present in this pathway, including Jak1, cause a number of different diseases, 33,34 and are responsible for numerous hepatocellular adenomas. 35 Additionally, the pathway is evolutionarily conserved and functions in transducing extracellular stimuli to the transcriptional apparatus.…”
Section: Resultsmentioning
confidence: 99%
“…31,32 Jak1 is a membrane protein whose kinase activity targets STAT proteins that are subsequently translocated to the nucleus to target specific gene transcription. Although most intensively studied for their important roles in cytokine signaling, modulating the immune response and oncogenesis, mutations in the proteins present in this pathway, including Jak1, cause a number of different diseases, 33,34 and are responsible for numerous hepatocellular adenomas. 35 Additionally, the pathway is evolutionarily conserved and functions in transducing extracellular stimuli to the transcriptional apparatus.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that SOCS3 proteins suppress the JAK/STAT signaling that triggers their expression . It seems that the strongest expression of SOCS proteins occurs in proximal tubule epithelia and glomerular cells.…”
Section: Discussionmentioning
confidence: 99%
“…With JAK–STAT pathways being highly enriched in shared networks between patients and murine models of DN [13], and with rodent models of both type 1 and type 2 diabetes DN displaying improved kidney function following JAK–STAT inhibitor treatment [32, 33], this signalling pathway appears to be a viable therapeutic target. Indeed, clinical trials targeting the JAK–STAT pathway are currently underway for treatment of DN [34]. There is also evidence demonstrating a role for JAK–STAT signalling in DPN progression.…”
Section: Discussionmentioning
confidence: 99%